Impact of pre-pregnant body mass index and gestational weight gain on the development of hypertensive disorders of pregnancy: the KODMO study - Yuka Matoba; Misato Ishikawa; Natsuo Tsutsumida; Kentaro Yamada; Naohiro Imazono; Kano Hayashi; Junki Abe; Kosuke Kawakami; Naofumi Ookura; Yoshihiro Ogawa (Endocrine Journal)
Obese pregnant women are more likely to develop hypertensive disorders of pregnancy (HDP), which puts them at risk for future cardiovascular events and type 2 diabetes. This study aimed to investigate the relationship between body weight and HDP in nondiabetic singleton-pregnant women. We examined the KODMO database, which included 5,120 pregnant women who gave birth at NHO Kokura Medical Center between January 2009 and December 2019, excluding those with pre-existing diabetes mellitus, hypertension, or multiple pregnancies. A multivariate logistic regression analysis of potential HDP risk factors revealed that both pre-pregnancy body mass index (BMI) and gestational weight gain (GWG) were independent risk factors. The estimated impact was considerably greater in women with higher pre-pregnancy BMI, with odds ratios of 1.60 (95% CI: 1.18–2.18, p = 0.0025) for obesity degree 1 (25 ≤ BMI < 30 kg/m2) and 3.42 (95% CI: 2.35–5.01, p < 0.0001) for obesity degree ≥2 (BMI ≥ 30 kg/m2) (reference: normal weight [18.5 ≤ BMI < 25 kg/m2]). GWG was further investigated by stratifying BMI categories, which revealed that obese pregnant women have a risk of developing HDP even with the normal GWG defined by current guidelines. The odds ratio of HDP in pregnant women with normal GWG was 1.79 (95% CI: 1.02–3.41, p = 0.0436) in obesity degree 1 and 3.25 (95% CI: 1.57–6.74, p < 0.0001) in obesity degree ≥2. The impact of GWG as a modifiable factor of HDP varies with pre-pregnancy BMI, highlighting the importance of weight management before and during pregnancy.